Hikmah knowledge capture insolvency on MSME responsibility and financial performance - Anna Widiastuti; Ibnu Khajar; Nunung Ghoniyah (Jurnal Siasat Bisnis, 2023)
Purpose – This study aimed to determine the extent to which the model of Hikmah Knowledge Capture Insolvency can be used as a solution in increasing knowledge and understanding good business financial management as a form of financial accountability in realizing better financial performance in addition to fill research gaps from previous research results. Design/Methodology/Approach – Respondents of this study were ATBM Weaving SMEs in Central Java. Researchers took three regencies as research objects, namely Jepara Regency, Pemalang Regency and Klaten Regency. A total of 110 respondents were selected by purposive sampling technique. The data was analyzed by using the Structural Equation Modeling (SEM) analysis technique with the application of Analysis Moment of Structural (AMOS.24). Finding – The results of the study explained that the dimensions of entrepreneurial orientation in this research variable included innovativeness, risk taking and proactivity. These variables supported the realization of financial responsibility and financial performance through understanding the conditions of liquidity difficulties (Hikmah Knowledge Capture Insolvency). Research Limitation/Implication – The measurement of Hikmah Knowledge Capture Insolvency in business financial management is only limited to SMEs weaving specifically ATBM. Practical Implication – The realization of financial responsibility in entrepreneurship orientation through the Hikmah Knowledge Capture Insolvency. Originality/Value – Using the basis of Capital Structure Theory, Knowledge Management through the concept of the Integrated Knowledge Management Cycle, and the values of Hikmah, the framework of this study is directed to address the influence between entrepreneurial orientation to financial performance through realization of Hikmah Knowledge Capture Insolvency and financial responsibility.